The implications of climate change scenario selection for future streamflow projection in the Upper Colorado River Basin - B. L. Harding; A. W. Wood; J. R. Prairie (Hydrology and Earth System Sciences, 2012)
The impact of projected 21st century climate conditions on streamflow in the Upper Colorado River Basin was estimated using a multi-model ensemble approach wherein the downscaled outputs of 112 future climate projections from 16 global climate models (GCMs) were used to drive a macroscale hydrology model. By the middle of the century, the impacts on streamflow range, over the entire ensemble, from a decrease of approximately 30% to an increase of approximately the same magnitude. Although prior studies and associated media coverage have focused heavily on the likelihood of a drier future for the Colorado River Basin, approximately 25 to 35% of the ensemble of runs, by 2099 and 2039, respectively, result in no change or increases in streamflow. The broad range of projected impacts is primarily the result of uncertainty in projections of future precipitation, and a relatively small part of the variability of precipitation across the projections can be attributed to the effect of emissions pathways. The simulated evolution of future temperature is strongly influenced by emissions, but temperature has a smaller influence than precipitation on flow. Period change statistics (i.e., the change in flow from one 30-yr period to another) vary as much within a model ensemble as between models and emissions pathways. Even by the end of the current century, the variability across the projections is much greater than changes in the ensemble mean. The relatively large ensemble analysis described herein provides perspective on earlier studies that have used fewer scenarios, and suggests that impact analyses relying on one or a few climate scenarios are unacceptably influenced by the choice of projections.